Monitoring of Land Use and Building Intensity in Manggarai Transit Oriented Development Area – Sub Area 1 - Irene Syona Darmady; Diana Presley; Raja Ananta Milala (Journal of Innovation and Community Engagement, 2025)
Cities are increasingly developing in various aspects as the population increases. Changes and developments in the City of Jakarta are taking place very rapidly. This can be seen clearly in terms of the expansion of the metropolitan area; the increase of the city network that facilitates population mobility, various architectural programs, and new projects in the city. In current conditions, the city government is trying to accommodate change and development of the city by developing spaces in Jakarta through the Transit Oriented Development system. This system aims to revitalize the area by promoting a new lifestyle that focuses on safe mobility and comfortable public transportation - a compact area with high intensity supported by various land uses. Manggarai is one of the such areas in Jakarta. Normally, an area such as the Manggarai area is encouraged to have a city design guideline document, so that development activities in the area follow the rules and directions. Due to the preparation of the guideline document by the DKI Jakarta Provincial Government, it is necessary to do a preliminary study to see the potential, challenges, and problems of the area. One of the aspects assessed in this process is the realization of land use and building intensity in existing/current conditions. The Untar community service team saw an opportunity to provide information on existing conditions (problems/challenges) and thoughts regarding the current situation in the Manggarai area, as input for consideration in the process of preparing the guideline document in the future. Field survey methods and comparative studies between existing conditions with detailed spatial plan document are used to assess realization/ fulfillment aspects.  The results of this service are booklets about growth and change, as well as challenges and problems in the Manggarai area. Growth of the Manggarai area is rapid, and there is an urge to have city guidance. This preliminary observation was submitted and presented to the Provincial Government Spatial Planning (Dinas Cipta Karya Tata Ruang dan Pertanahan Pemprov DKI Jakarta).